A comparison between aerial mass colors, antibacterial activities and RAPD fingerprints of soil isolates of streptomyces - Zarizal, Suhaili (2012)
This study compared the distribution of aerial mass colors, antibacterial activities and RAPD-based genomic patterns of 39 Streptomyces isolates harvested mainly from soil at the University Agricultural Park. Unrversiti Putra Malaysia. Streptomyces gnseus ATCC 10137 strain was also included as a reference strain (n = 40) Based on ISP-2 media the aerial mass colors observed were categorized as yellow (n = 15) grey (n = 9). brown (n = 7) white (n = 6) and others In = 3) Antibacterial activities were assessed on Mueller Hinton Agar (MHA) and Tryptic Soy Agar (TSA) by perpendicular streak method against Staphylococcus aureus ATCC 26923. Eschenchia cob ATCC 25922 Salmonella sp and Enterococcus sp. MHA demonstrated 15 isolates with broad spectrum antibacterial actMties and 18 as non-broad spectrum TSA gave lower proportions with 15 and 9 isolates respectwely Regardless of the test media used a higher proportion of isolates with non-white color showed antibacterial activities to suggest a potential correlation RAPD dendrogram (a composite of 3 random primers) also clustered majority of them but segregated those of white color. which showed less antibacterial activities. in a different cluster. Further validations involving more isolates are warranted to establish the findings. 0 2012 Asian Network for Scientific Information